Optimal reactive power dispatch using modified-ant lion optimizer with flexible AC transmission systems devices - Chaitanya, Sela Naga Venkata Sri Krishna; Bakkiyaraj, R. Ashok; Rao, Bathina Venkateswara; Jayanthi, Kalikrishnan (Bulletin of Electrical Engineering and Informatics, 2025)
This study focuses on reactive power planning in the IEEE30-bus test system, specifically involving the integration of flexible AC transmission systems (FACTS) within the utility system. The primary objective is to minimize power loss and voltage deviation. To address this, a recently developed optimization algorithm called modified ant-lion optimizer (MALO) is applied to solve the optimal reactive power dispatch (ORPD) problem on the IEEE 30-bus system. A comparative analysis is conducted between the results obtained with and without FACTS devices. The findings reveal that the utilization of FACTS devices leads to significantly improved outcomes compared to scenarios without FACTS devices. Among the FACTS devices studied, the unified power flow controller (UPFC) demonstrates superior performance compared to the static synchronous compensator (STATCOM) and interline power flow controller (IPFC).